The prevalence of Toxoplasma infection in hospitalized patients in selected hospitals of Kerman. - H Keshavarz; S Mamishi; H Daneshvar (Journal of Kerman University of Medical Sciences, 2000)
Toxoplasmosis is a disease caused by a ubiquitous,obilgate intrace;;ular protozoan"Toxoplasma gondii".the present study was undertaken to determine the prevalence of Toxoplasma infection in Kerman province of Iran.Atotal of 690 bllod samples,collected from patients in Kerman hospitals were serologically tested by indirect fluorescent antibody technique(IFA) for Toxoplasma antibadies.46.9 percent of the samples were found positive with antibody titers of 1:16 and higher.for nall ages the prevalence in males(48.6%) is not significantly different from the prevalence of 44.9% in females.Although there seems be a trend toward increasing seropositivity with increasing age,there was no statistical significance increas in the prevalence of seropositivity with increasing age.the highest prevalence rate (52.5%) was observed in the age group of 10-19 years with GMRT (Geometric Mean of reciprocal titer)77-4.noassociation was found between the seropositivity rate and contact with domestic cats.also,there was no significant correlation between the consumption of improperly cooked meat and seropositivity rates.